A Gender-Just Perspective on the Qur’anic Narrative of Adam and Eve: Creation, Relationality, and Descent to Earth - Jahira Salsabila Nurul Imam (Yinyang: Jurnal Studi Islam Gender dan Anak, 2025)
This study reexamines the Qur’anic narrative of the creation, relationship, and descent to earth of Adam and Eve through a gender-just interpretive framework. Classical interpretations have often portrayed women as secondary beings or as the primary cause of humanity’s misfortune, views largely shaped by patriarchal assumptions rather than grounded in the Qur’anic text itself. Employing a literature-based qualitative approach and a thematic exegesis (tafsīr maudhu‘ī), this study examines key Qur’anic verses including Surah 4:1, 7:11–27, 20:115–122, and 39:6, by comparing traditional exegetical perspectives with contemporary gender-sensitive interpretations. The findings demonstrate that the Qur’an affirms the ontological equality of men and women through the concept of nafs wāḥidah (a single shared essence) and does not attribute exclusive responsibility for humanity’s earthly descent to Eve. This article contributes to Qur’anic gender studies by reconstructing the Adam–Eve narrative as one that emphasizes collective moral responsibility and mutuality, in accordance with the Qur’an’s broader principles of justice, reciprocity, and gender equality.